MODAL SOSIAL PESANTREN JAWA PESISIRAN UTARA DALAM PEMBERDAYAAN MASYARAKAT - A. Zaenurrosyid; Ahmad Nuruddin (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
Kiai and pesantren are acknowledge to have contributed a lot in solving the problems of community welfare, especiallyin socio-religious and economic matters in Indonesia. The existence of pesantren so far has not only been insulated on its duties in managing morals and arranging itself as a tafaqquh fiddin institution that is indifferent to various social dynamics that develop. On the contrary, pesantren are actually responsive and progressive in addressing these issues with concrete work in the direct grassroots realm. Kiai Sahal and Maslakul Huda are examples of how kiai and pesantren figures institutionally contribute to answering social issues. Various activities carried out by the Maslakul Huda Islamic Boarding School are a form of crystallization of Kiai Sahal's ideas in order to respond to the actual social problems of the lower class of Kajen Village and its surroundings. Norms, the social networks in the figure of Kiai Sahal and the Pesantren Maslakul Huda, in this case have succeeded in fostering public trust which in the later stages has made it easier for the Islamic Boarding School Maslakul Huda to instill religious values ​​in their communities. This study tries to see how the social capital in Kiai Sahal and the Islamic Boarding School Maslakul Huda is able to bring success in realizing community welfare. The results of this study mention that community empowerment carried out by Kiai Sahal and the Pesantren Maslakul Huda participated in the process of transforming people's welfare through various activities and institutions under the auspices of the Maslakul Huda Islamic Boarding School Foundation.